Oral manifestations in young adults infected with COVID-19 and impact of smoking: a multi-country cross-sectional study - El Tantawi, Maha; Sabbagh, Heba Jafar; Alkhateeb, Nada Abubakor; Quritum, Maryam; Abourdan, Joud; Qureshi, Nafeesa; Qureshi, Shabnum; Hamoud, Ahmed; Mahmoud, Nada; Odeh, Ruba; Al-Khanati, Nuraldeen Maher; Jaber, Rawiah; et al. (PeerJ, 2022)
Background Oral manifestations and lesions could adversely impact the quality of people’s lives. COVID-19 infection may interact with smoking and the impact on oral manifestations is yet to be discovered. Objectives The aim of this study was to assess the self-reported presence of oral lesions by COVID-19-infected young adults and the differences in the association between oral lesions and COVID-19 infection in smokers and non-smokers. Methods This cross-sectional multi-country study recruited 18-to-23-year-old adults. A validated questionnaire was used to collect data on COVID-19-infection status, smoking and the presence of oral lesions (dry mouth, change in taste, and others) using an online platform. Multi-level logistic regression was used to assess the associations between the oral lesions and COVID-19 infection; the modifying effect of smoking on the associations. Results Data was available from 5,342 respondents from 43 countries. Of these, 8.1% reported COVID-19-infection, 42.7% had oral manifestations and 12.3% were smokers. A significantly greater percentage of participants with COVID-19-infection reported dry mouth and change in taste than non-infected participants. Dry mouth (11.1% vs 7.5%, p = 0.009) and change in taste (11.5% vs 2.7%, p < 0.001) were greater in COVID-19 infected than non-infected persons. The association between COVID-19-infection and dry mouth was stronger among smokers than non-smokers (AOR = 1.26 and 1.03, p = 0.09) while the association with change in taste was stronger among non-smokers (AOR = 1.22 and 1.13, p = 0.86). Conclusion Dry mouth and changed taste may be used as an indicator for COVID-19 infection in low COVID-19-testing environments. Smoking may modify the association between some oral lesions and COVID-19-infection.
Keywords: COVID-19; Oral lesions; Smoking; Dry mouth